Prevalence of infectious and non-infectious diseases in cattle population in Chittagong district of Bangladesh - Badruzzaman, A. T. M.; Siddiqui, Md. Saiful Islam; Faruk, Md. Omer; Lucky, Nasrin Sultana; Zinnah, Mohammad Ali; Hossain, Ferdaus Mohd. Altaf; Rahman, Md. Masudur (International Journal of Biological Research, 2014)
Background: Cattle are affected by many infectious and noninfectious diseases that can lead to economic losses to the farmers in terms of reduced growth and production performance and mortality.Objectives: This study was conducted to investigate the prevalence of infectious and noninfectious diseases of cattle in Chittagong district of Bangladesh.Methods: A total of 2614 clinical cases were diagnosed at five different veterinary hospitals in Chittagong district of Bangladesh during the year 2013. Disease diagnosis was made on the basis of owner’s statement, general examination, clinical signs, gross pathology, and laboratory procedures. Data were analyzed to determine disease prevalence in cattle with respect to breed, sex and season.Results: Diagnosed diseases were categorized as infectious diseases, parasitic diseases, digestive disorders, metabolic diseases, respiratory diseases and other diseases. According to our results, the prevalence of digestive disorders was the highest (45.14%) followed by parasitic diseases (30.64%), infectious diseases (9.49%), respiratory diseases (3.90%), metabolic diseases (3.18%) and other diseases (3.18%). Disease prevalence was highest in Cross-bred cattle (44. 23%) followed by Red Chittagong cattle (28.46%) and Non-descript Deshi (27.31%). Female were more susceptible to diseases (54.32%) than male cattle (45.68%). Disease prevalence varied according to seasons. Highest prevalence was recorded in summer season (37.49%) followed by rainy season (34.81%) and winter season (27.70%).Conclusions: Our large set of data on cattle disease prevalence in Chittagong district of Bangladesh provides valuable insight to design and implement priority based research on specific disease and to take efficient control strategies against the diseases.